Assessment of Sensorimotor Behaviour in Konzo-Induced Rats Using the Irvine, Beattie Bresnahan Forelimb Scale - David, Lekpa Kingdom; Uahomo, Precious Ojo; Idung, Victor Hogan; Dakoru, Rachael Data (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
Konzo is a neurological disorder of selective upper motor neurons. It is an irreversible paralytic disease associated with prolonged consumption of Cassava. It contains cyanogenic glycosides metabolized to hydrogen cyanide, which has been shown by studies to affect the motor neurons of the central nervous system. The Irvine, Beattie Bresnahan (IBB) scale is a recently developed forelimb scale for the assessment of fine control of the forelimb and digits after cervical spinal cord injury such as Konzo. 20 Adult male Wistar rats were assigned to 4 experimental groups (i) control n=5, (ii) konzo-induced group n=5, (iii) induced + Complan n=5 (iv) Induced + Bambara Nut (Okpa). The bitter cassava foods were taken by oral ingestion for a period of 4 weeks. The assessment of the forelimb and digits were done using the Irvine, Beattie Bresnahan (IBB) with specific parameters such as Predominant Elbow Joint movement, Contact Volar Support, and Grasping method. The body weight of the animals was also recorded every week. The data obtained were analyzed using ANOVA. The result obtained showed that there was a significant difference (p<0.05) between the body weight of the animals induced with Konzo and rehabilitated with Complan milk and Bambara nut when compared to the unrehabilitated Konzo-induced group. There were differences in the results of the parameters being tested for the Irvine, Beattie Bresnahan (IBB) scaling. The IBB scale confirmed that there was a high level of cyanide content in the cassava which affected the behavioral attributes of the induced group and it also confirmed that the induced group can be ameliorated with the use of Complan and Bambara Nut (Okpa) which was shown in the parameters being tested such as Predominant Elbow Joint movement, Contact Volar Support, and Grasping method. It was concluded that insufficiently processed bitter cassava is toxic and has neurotoxicity effects on the Spinal Cord especially on the upper motor neurons and IBB scale is capable of measuring gradual improvements in motor forelimb functions in this model and may be a new and effective assessment tool for peripheral nerve injury.